2017
DOI: 10.4172/2151-6200.1000265
|View full text |Cite
|
Sign up to set email alerts
|

China-Pakistan Economic Corridor and Its Social Implication on Pakistan: How Will CPEC Boost Pakistan’s Infrastructures and Overcome the Challenges?

Abstract: This paper discusses the China-Pakistan Economic Corridor (CPEC) long-term infrastructural project as a major part of the One Belt One Road (OBOR) the major global initiative by the Chinese government, scheduled to complete by 2030. CPEC is a joint project that Beijing and Islamabad agreed to finance through Chinese investments utilizing investment loans largely by Chinese financial institutions; nevertheless, Pakistan will also be responsible for investing approximately 15 billion dollars on its own in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 1 publication
(1 reference statement)
0
34
0
1
Order By: Relevance
“…CPEC is the name of several infrastructures, economic development, industrial zones, and regional connectivity projects that are presently under construction throughout Pakistan (Ahmad & Hong, ). Past scholars and policymakers have demonstrated that the CPEC project decreases unemployment by generating millions of employment opportunities (Ali & Qazi, ; Chen et al, ), brings in new business and provides new investment opportunities (Raza, ; Wajeeh & Yang, ), provides opportunities for large‐scale business and small businesses (Rehman et al, ), and generates revenue for host communities (Raza et al, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…CPEC is the name of several infrastructures, economic development, industrial zones, and regional connectivity projects that are presently under construction throughout Pakistan (Ahmad & Hong, ). Past scholars and policymakers have demonstrated that the CPEC project decreases unemployment by generating millions of employment opportunities (Ali & Qazi, ; Chen et al, ), brings in new business and provides new investment opportunities (Raza, ; Wajeeh & Yang, ), provides opportunities for large‐scale business and small businesses (Rehman et al, ), and generates revenue for host communities (Raza et al, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Then after reaching the shores, the oil is transported to various provinces of China, which almost doubles the overall transportation cost, making it very expensive. The CPEC project will be the alternative fastest and safest route for Chinese businesses, which will reduce the distance from approximately 12,500 to CPEC is the name of several infrastructures, economic development, industrial zones, and regional connectivity projects that are presently under construction throughout Pakistan (Ahmad & Hong, 2017). Past scholars and policymakers have demonstrated that the CPEC project decreases unemployment by generating millions of employment opportunities (Ali & Qazi, 2018;Chen et al, 2018), brings in new business and provides new investment opportunities (Raza, 2018;Wajeeh & Yang, 2018), provides opportunities for large-scale business and small businesses (Rehman et al, 2018), and generates revenue for host communities .…”
Section: China-pakistan Economic Corridormentioning
confidence: 99%
“…They have opposed CPEC on the grounds that it will further strengthen the circle of exploitation emerging from the center-this time in collaboration with a foreign state (Ahmad and Hong, 2017;Mengal, 2016). The Baluch separatists and militants have shown their opposition to CPEC by carrying out various acts of sabotage such as, target killing and abduction of Chinese workers and blasts targeting CPEC project sites or infrastructure.…”
Section: Cpec and Politics Of Regionalismmentioning
confidence: 99%
“…Provincial Assembly of Khyber Pakhtunkhwa (KPK) rejected prioritization of Eastern route and passed resolution opposing any route change, since the original route holds the promise of benefitting the underdeveloped areas of KPK (Mengal, 2016;Ahmad and Hong, 2017). Aftab Ahmed Sherpao, leader of the Qaumi Watan Party-the party that emerged as the fourth largest party in KPK in the 2013 General Electionsexpressed his concerns about the national outreach of CPEC in a parliamentary committee meeting held in October 2016 (Raza, 2016).…”
Section: Cpec and Politics Of Regionalismmentioning
confidence: 99%
“…Through CPEC China will build a 3000 km network of ports, terminals, roads, railways and oil & gas pipelines extending its way from coastal area of Gwadar city to the historic city of Kashgar in northwestern China (Bader, 2015). Ahmad and Mi (2017) in their study investigated the impact of CPEC on infrastructural development within Pakistan. They found out that CPEC is indeed good news for the countries and it has positive impacts as far as the country's economic problems are concerned.…”
Section: Literature Reviewmentioning
confidence: 99%